Pengaruh Strategi Pemasaran Islami Terhadap Keputusan Pembelian Thrifting di Instagram pada Masyarakat Surabaya - Maolina Nurdin (Nomicpedia: Journal of Economics and Business Innovation, 2021)
The purpose of this research is the influence of Islamic marketing strategies on purchasing decisions on Instagram thrifting in the Surabaya community. The research approach is quantitative. The variables used are Islamic marketing strategy (X) and purchasing decisions (Y). The population used is the people of Surabaya who are interested in thrifting, with the sampling technique using purposive sampling, then the population is calculated using the solving formula to determine the number of samples. Using secondary data and primary data with data collection techniques using google forms and respondents' answers were measured using a Likert scale. The goodness of the questionnaire was tested using validity and reliability tests. This study produces a significant Islamic marketing strategy and has a positive effect on thrifting purchasing decisions. The coefficient of determination (R2) is 0.764, which means that the Islamic marketing strategy variable has a 76.4% percentage of influence on thrifting purchasing decisions on Instagram in the people of Surabaya.